Catalyst-induced enhancement of direct methane synthesis in solid oxide electrolyser. (20th September 2021) - Biswas, Saheli; Kulkarni, Aniruddha P; Fini, Daniel; Singh Rathore, Shambhu; Seeber, Aaron; Giddey, Sarbjit; Bhattacharya, Sankar
Highlights: Catalytic effect of Fe on in-situ methanation in a solid oxide electrolytic cells (SOEC) was investigated using Fe–Ag and Fe–GDC–Ag electrodes. With Fe–Ag electrodes, gaseous mass transport and CO2 electrolysis were the rate-limiting steps at lower and higher potentials, respectively. GDC addition improved CO2 electrolysis and altered Fe work function, increasing methane yield. Different iron phases present on the cathode affect the electrochemical performance of the SOEC Abstract: CO2 valorisation to fuels and chemicals in solid oxide electrolytic cells (SOECs) has been a topic of great interest for the past few years. Methane is one such highly valuable fuel, but its in-situ generation in SOECs is an emerging technology. For the first time, we explain how the introduction of a methanation catalyst metal into the cathode affects the electrokinetics of in-situ methane generation in an electrolyte-supported symmetric tube cell while electrolysing a mixture of H2 /CO2 . Fe–Ag and Fe–GDC–Ag electrodes were studied in the applied voltage range of 1.3–1.8 V and temperature range of 500–700°C. While Fe guaranteed good catalytic activity towards methanation reactions, Ag ensured good electrical conductivity of the electrode. Addition of GDC to the cathode remarkably improved CO2 electrolysis and modified Fe work function under loaded conditions, thus increasing methane generation to a maximum of 2.5% at 600°C and 1.6 V. For the Fe–Ag electrode, gaseous mass transport at the cathode was the rate-limiting step up to 1.4 V, whereas at higher potentials, CO2 electrolysis at the triple-phase boundary became the rate-determining step. Short-term cell testing at 1.7 V and 500°C revealed the presence of a Fe3 C phase on the cathode, which affected the electrochemical performance of the cell. Graphical abstract: Image, graphical abstract